Eco-friendly Process to Degum Flax Roving with Deep Eutectic Solvent and Microbial Treatment. Issue 14 (28th October 2022) - Xiang, Mengxiong; Li, Yanrong; Shu, Tong; Wang, Huihui; Li, Pandeng; Yu, Tianyi; Yu, Longjiang
ABSTRACT: Flax is an economically important fiber crop, however, it requires degumming to yield usable fibers. The degumming process of flax roving is a key step in flax processing and production. In this study, deep eutectic solvent (DES; choline chloride–urea) pretreatment was combined with microbial treatment to develop an ecofriendly and effective degumming method for flax roving. The optimal conditions for DES pretreatment (100°C for 120 min with 90% DES) were obtained through orthogonal tests. DES combine microbial treatment could effectively remove gum from the flax fibers. The flax roving fibers were characterized by chemical analyses, scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffractometry, and thermogravimetric analysis. Compared with fibers treated with microbes alone, flax roving fibers subjected to DES combine microbial treatment showed better breaking tenacity (16.77 cN/tex) and average pectin, hemicellulose, and lignin removal rates of approximately 86.4%, 26.7%, and 55.1%, respectively. NMR revealed that the composition of DES was not damaged during pretreatment, which means the bulk solution could be reused. This research showed that DES combine microbial treatment is feasible and effective method for flax roving degumming.